Contemporary feminist perspectives - Guhathakurta, Meghna (Dhaka : University Press, 1997)
Papers presented at a workshop held in 1994.
Includes bibliographical references and index.
ESS, BIED
Complimentary copy from Professor Dr. Nasreen Khundker, Complimentary copy from BIED
Keywords: Women's studies -- Bangladesh; Feminism -- Bangladesh; Women -- Bangladesh -- Social conditions